Nitric Oxide. Part C, Biological and Antioxidant Activities;Vol-301 - Packer, Lester (Methods in Enzymology, 1999)
Offers coverage of different tools for the elucidation of Nitric Oxide action. This volume highlights techniques for researching the physiology and toxicity of nitric oxide in cellular and organismal systems.